Spectra and Oscillator Strengths of $d$-$d$ and $d$-$p$ Transitions for Cobalt-Like $Cd^{21+}$ Ion (Journal of Atomic and Molecular Sciences, 2011)
We calculate the spectra and oscillator strengths for highly ionized cobalt-like $Cd^{21+}$ ions $3p^63d^9-3p^53d^{10},$ $3p^63d^9-3p^63d^84p$ transitions by using multi-configuration self-consistent field method program together with fitting formula proposed by us. The calculations have a good agreement with observations.
Keywords: highly ionized; energy level; fitting formula.